KODIFIKASI HADIS NABI PRESPEKTIF IMAM KHATIB AL-BAGHDADI DALAM KONTEKS PENDIDIKAN AGAMA ISLAM - M.Taufiq Hidayat; Muhid; Andris Nurita (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2023)
This research discusses the codification of Prophetic hadith from the perspective of Imam Khatib Al-Baghdadi in the context of Islamic Religious Education. The urgency of this article is to emphasize the importance of the codification of the Prophet's hadith in the context of Islamic religious education. The method in this writing uses a qualitative approach with data collection methods through literature study. The Prophet's hadith as the second source of law after the Koran plays an important role in the process of legal istinbath in Islam. Codification of the Prophet's hadith is the process of collecting, compiling, and organizing the Prophet's hadith so that they can be used as a valid and trustworthy source of law. Imam Khatib Al-Baghdadi succeeded in explaining discussions in the science of hadith systematically and in language that is dense in meaning so that it is easy to understand. Imam Khatib Al-Baghdadi also discussed and refuted the thoughts of Orientalists with arguments that he built naqli and aqli. In the context of Islamic religious education, the codification of the Prophet's hadith also has a very important role for Islamic students and teachers to study and understand the codification of the Prophet's hadith to distinguish between authentic and false hadith.